The effect of N-methylation of amino acids (Ac-X-OMe) on solubility and conformation: a DFT study. Issue 39 (20th August 2015) - Md. Abdur Rauf, Shah; Arvidsson, Per I.; Albericio, Fernando; Govender, Thavendran; Maguire, Glenn E. M.; Kruger, Hendrik G.; Honarparvar, Bahareh
Abstract : N -Methylation of amino acid derivatives (Ac-X-OMe, X = Gly, Val, Leu, Ile, Phe, Met, Cys, Ser, Asp and His) leads to an increase in aqueous solubility, lipophilicity and lowering of the cis / trans amide conformational energy barrier ( E A ). Abstract : N -Methylation has a significant impact on improving the oral bioavailability, lipophilicity and aqueous solubility of peptide-based lead drug structures. The selected mono-amino acid derivatives Ac-X-OMe, where X = Gly, Val, Leu, Ile, Phe, Met, Cys, Ser, Asp and His as well as their corresponding N -methylated analogues were studied. The clog  P values of all N -methylated peptides are greater than those of native compounds. Quantum chemical calculations were performed to estimate the aqueous solubility of these lipophilic compounds using density functional theory (DFT). To confirm the contribution of dispersion forces on quantum chemical data, the long-range corrected (LC) hybrid density functional (ωB97X-D) was also probed for some amino acid derivatives. The ωB97X functional gave similar results. Our results reveal that after mono N -methylation of the peptide backbone, Δ G solv becomes more negative (more water soluble) while polarizability and dipole moment are also increased. Natural atomic charges derived by natural bond orbital (NBO) analysis of N, C, and O atoms involved in amide functional group become more positive/(less negative) after N -methylation. All N -methylated amino acids have higher E HOMO (less negative) in comparison with the amino acid analogues, and in all cases N -methylation decreases E HOMO–LUMO . The calculated amide cis / trans activation energies ( E A ) of all the N -methylated amino acid derivatives were lower than that of native species. N -methylation of these compounds leads to an increase in lipophilicity, aqueous solubility, polarization, dipole moment and lowering of the cis / trans amide energy barrier ( E A ).